Haplotype-specific expression of the N-terminal exons 2 and 3 at the human MAPT locus - Caffrey, Tara M. (2007)
The microtubule associated protein tau (MAPT) H1 haplotype shows a strong association to the sporadic neurodegenerative diseases progressive supranuclear palsy and corticobasal degeneration. The functional biological mechanisms behind the genetic association have started to emerge with differences recently shown in haplotype splicing of the neuropathologically relevant exon 10. Here we investigate the hypothesis that expression of the alternatively spliced N-terminal exons also differs between the two MAPT haplotypes. We performed allele-specific gene expression analysis on a H1/H2 heterozygous human neuronal cell line model and 14 H1/H2 heterozygous human post-mortem brain tissues from two brain regions. In both cell culture and post-mortem brain tissue, we show that the protective MAPT H2 haplotype significantly expresses two-fold more 2N (exons 2+ 3+) MAPT transcripts than the disease-associated H1 haplotype. We suggest that inclusion of exon 3 in MAPT transcripts may contribute to protecting H2 carries from neurodegeneration.